The branch will not break : poems - Wright, James, 1927-1980 (Wesleyan University Press, 1963)
A new book of poetry from a Pulitzer Prize-winning master poet.
Keywords: American poetry.; American poetry -- 20th century.; Poésie américaine.; Poésie américaine -- 20e siècle.; POETRY -- American -- General.; American poetry; 1900 - 1999